PPAR𝛾 and Agonists against Cancer: Rational Design of Complementation Treatments - Dorina Veliceasa; Frank Thilo Schulze-Hoëpfner; Olga V. Volpert (PPAR Research)
PPAR𝛾 is a member of the ligand-activated nuclear receptor superfamily: its ligands act as insulin sensitizers and some are approved for the treatment of metabolic disorders in humans. PPAR𝛾 has pleiotropic effects on survival and proliferation of multiple cell types, including cancer cells, and is now subject of intensive preclinical cancer research. Studies of the recent decade highlighted PPAR𝛾 role as a potential modulator of angiogenesis in vitro and in vivo. These observations provide an additional facet to the PPAR𝛾 image as potential anticancer drug. Currently PPAR𝛾 is regarded as an important target for the therapies against angiogenesis-dependent pathological states including cancer and vascular complications of diabetes. Some of the studies, however, identify pro-angiogenic and tumor-promoting effects of PPAR𝛾 and its ligands pointing out the need for further studies. Below, we summarize current knowledge of PPAR𝛾 regulatory mechanisms and molecular targets, and discuss ways to maximize the beneficial activity of the PPAR𝛾 agonists.